Adaptive Capacity of Brantas Watershed in Malang City Fancing of the Climate Change Impact - Dwi Prihanto; Arief Rachmansyah; Harsuko Riniwati (Graduate Program, 2019)
The impact on global warming is the occurrence of climate change that affect the condition of watershed ecosystem (DAS). This condition causes a decline in the level of community welfare and increases the level of community vulnerability. Furthermore, these ecological changes may have an effect on the adaptive capacity of community living in the watershed area. This paper raised the issue of climate change that occurred in the Brantas watershed society of Malang city. Adaptive capacity has an important role in addressing and minimizing vulnerability in an area. This study aims to analyze the level of adaptive capacity community on climate change. This type of research is classified as a quantitative descriptive where data acquisition and processing are derived from secondary data of regional device organization classified into several parameters and indicators then processed using weighted scale and displayed in spatial maps. This paper shows that the phenomenon of climate change has been significantly felt by the people living in the Brantas watershed. Nevertheless, these symptoms have not been considered a significant problem by the community. This is influenced by limited knowledge of the symptoms of climate change. Other findings show that adaptive capacity is not only determined by environmental conditions. The social structure of both patron-client and institutional relationships at the village level is very influential on the adaptive capacity of the Brantas watershed of Malang city.Keywords: Adaptive capacity, Brantas watershed, Climate change, Malang city, GIS, Social structur